Prescription for the people : an activist's guide to making medicine affordable for all - Quigley, Fran, 1962- (Culture and politics of health care work., 2017)
In Prescription for the People, Fran Quigley diagnoses our inability to get medicines to the people who need them and then prescribes the cure. He delivers a clear and convincing argument for a complete shift in the global and U.S. approach to ...